Pengaruh Kebiasaan, Disiplin dan Fasilitas Belajar Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Ekonomi - Aprilia, Innayati; Afriza, Edi Fitriana; Gumilar, Rendra (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The research was motivated by the low learning outcomes of students in economic subjects. This study aims to determine the effect of Study Habits, Learning Discipline and Learning Facilities on Learning Outcomes both partially and simultaneously. This research method uses an explanatory survey method. The research was conducted at SMA Negeri 1 Ciawi with a population of 440 students. The sampling technique probability sampling type proportional simple random sampling using the slovin formula, obtained a sample of 209 students. data collection techniques using questionnaires and analyzed with multiple linear analysis techniques. The results of hypothesis testing show that 1) study habits have a significant effect on learning outcomes with a tcount value of 3.861, 2) learning discipline has no effect on learning outcomes. Learning discipline has no effect on learning outcomes with a tcount value of 1.463 3) Learning facilities have a significant effect on learning outcomes with a tcount value of 2.770 and 4). Learning habits, learning discipline and learning facilities simultaneously affect learning outcomes with Fhitung> Ftabel 25.821>3.03972. Based on the results of testing the coefficient of determination, it shows that study habits, learning discipline and learning facilities have an influence on learning outcomes by 27.4%.